A Proposal for the Creation of “Los Chorotegas Ecomuseum” in the Matambú Indigenous Territory, Guanacaste, Costa Rica - Murillo, Cinthya (2024)
Over time, human geography has played a fundamental role in communities’ processes of adaptation to their environment. This involves considerations spanning the modification of territories, social organization, and economic activities such as cultural tourism. This also involves understanding the geographic context of their history and culture to add value to communities’ knowledge and processes. Therefore, this article proposes the creation of a Chorotega Culture Eco-Museum in Matambú, a community located within the South Guanacaste Unit of Touristic Planning, Costa Rica. This proposal arises from the necessity of this indigenous community to be part of the tourism industry as a survival strategy. The objective is to promote ecotourism and cultural and creative tourism in the Matambú Chorotega Indigenous Territory (TICM). This initiative serves as a method to enhance the socio-economic conditions of the indigenous community while helping to preserve and rescue the sense of belonging to its cultural and natural heritage.  By achieving the objective of creating “Los Chorotegas” Eco-Museum in the Matambú community, this territory and indigenous group will be respected and valued as the only remaining ethnicity of Mesoamerican origin within Costa Rica, and this recognition can improve their quality of life.